Camping-related carbon monoxide poisoning: knowledge and risk behaviors among young Saudi campers - Aldobeaban, Sarah Mohamed; Alyahya, Ahmed Ibrahim; Samah Fathy Ibrahim; Alrussayes, Saja Saad; Elserafy, Osama Saeid (Journal of the Pakistan Medical Association, 2022)
Objectives: To evaluate the Saudi campers’ knowledge and the applied safety practices regarding carbon monoxide poisoning during camping activities. Method: The cross-sectional questionnaire-based study was conducted from December 1, 2018, to February 1, 2019, in Riyadh, Saudi Arabia, and comprised young male campers from recreational camps in the northern parts of the city. Data was collected from the participants regarding socio-demographic characteristics, knowledge regarding carbon monoxide poisoning, the applied safety measures to prevent carbon monoxide poisoning and the dealing with carbon monoxide poisoning during camping activities. Data was analysed using SPSS 22. Results: There were 235 male subjects with mean age 24.47±1.139 years (range: 21-32 years). Of the total, 50(21.3%) participants had received civil defence education or training. Overall, 137(58.3%) participants had a good mean knowledge score, and 157(66.8%) participants had a good mean practice score for applying healthy measures in preventing and managing carbon monoxide poisoning. As a preventive measure against carbon monoxide poisoning, the use of carbon monoxide detectors was valued by 107(45.5%) participants. Having civil defence training, having a monthly income >10,000 Saudi Riyals, and having a good knowledge score were the elements that had significant association with the choice related to carbon monoxide detector usage. Conclusion: The campers had relatively high knowledge regarding carbon monoxide poisoning, but this knowledge was not fully translated into good health practice. Key Words: Environmental toxin, Camping, Carbon monoxide poisoning, Knowledge, Practice.